P-36 Brumyodo – a birmingham dying matters community. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Hudson, Sharon; Weeks, Carrie; Glover, Frances; Locke, Anna; Tooley, Laura; Mitchell, Sarah; Smith, Laura
Abstract : BrumYODO is a social movement which emerged over a belief and commitment to achieving better dying in Birmingham. We are a collective of undertakers, artists, craftivists, hospices, doctors, nurses and citizens of Birmingham. For Dying Matters Week we planned and delivered a huge range of activities to engage our community in conversation about death and dying- with the message that talking about it won't make it happen (as Ellie our celebrant says. Just like eating lettuce won't make you thinner). Our social media campaign, run with good will and energy, has generated passion, networks and the #BigConversation with a reach of thousands. Events included, five death cafes, a pop-up shop with multiple contributors, coffin design, storytelling, philosophy and a Death Disco. Images and creativity have threaded with practical sessions – engaging hearts and minds. We have filmed events to create a film to share in GP surgeries and primary care. We are true grassroots collaboration and the networks we have created will be sustained well into our future.